Persistent Skin Symptoms after Diagnosis and on a Long-term Gluten-free Diet in Dermatitis Herpetiformis - Camilla Pasternack; Kaisa Hervonen; Eriika Mansikka; Timo Reunala; Pekka Collin; Katri Kaukinen; Teea Salmi (Medical Journals Sweden, 2021)
Dermatitis herpetiformis is a cutaneous manifestation of coeliac disease treated with a gluten-free diet. However, the itching and blistering rash alleviates slowly after gluten withdrawal and occasionally persists despite a long-term gluten-free diet. This study investigated the prevalence and factors associated with prolonged (i.e. >2 years) and ongoing skin symptoms in 237 patients with dermatitis herpetiformis. Data were gathered from medical records and via questionnaires. Among patients with dermatitis herpetiformis, 38% had prolonged symptoms after diagnosis, and 14% had ongoing skin symptoms at follow-up (median duration of gluten-free diet 24 years). A severe rash at diagnosis was associated with both prolonged and ongoing cutaneous symptoms. In addition, patients with dermatitis herpetiformis with ongoing skin symptoms at follow-up had been on the dietary treatment for a shorter time (median duration 16 vs 25 years) and were less often on a strict diet (53% vs 78%) compared with patients with dermatitis herpetiformis without ongoing skin symptoms.